Hydrophosphorylation of aliphatic alkynes catalyzed by CuNPs/ZnO for the synthesis of vinyl phosphonates: a DFT study on the reaction mechanism - Fortunato, Leandro Federico (2017)
The reaction mechanism of the CuNPs/ZnO-catalyzed hydrophosphorylation of aliphatic alkynes for the synthesis of vinyl phosphonates has been investigated. Based on experimental observations and theoretical calculations through DFT studies, a reaction mechanism is proposed, in which a crucial role of both the solvent and the catalyst support is suggested. DFT studies and experimental data, are consistent with a reaction mechanism based on a copper-catalyzed anti-Markovnikov hydrophosphorylation process that favours the formation of the vinyl phosphonate E isomer.